Measuring the Technical Efficiency of Farms Producing Environmental Output: Parametric and Semiparametric Estimation of Multi-output Stochastic Ray Production Frontiers - Tomasz Gerard Czekaj (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
This paper investigates the technical efficiency of Polish dairy farms producing environmental output using the stochastic ray function to model multi-output – multi-input technology. Two general models are considered. One which neglects the provision of environmental output and one which accounts for such output. Three different proxies of environmental output are discussed: the ratio of permanent grassland (including rough grazing) to total agricultural area, the total area of permanent grassland and the amount of environmental subsidies which farmers are paid for providing environmental goods and services. These proxies are discussed on the basis of microeconomic production theory and are empirically compared by the econometric approach using parametric and semiparametric stochastic frontier models. The main focus is on the estimation of technical efficiency of farms producing the environmental output. Since some farms do not provide such output at all, the stochastic ray frontier functions are estimated to overcome the problem of the zero valued dependent variables which often occur when the Translog output distance function is used. The detailed results of the technical efficiency analysis show that, although the estimated efficiencies from the models which neglect the environmental output and those which account for the output are rather similar on average, the rankings based on these efficiencies differ. Finally, based on the theoretical economic reasoning and empirical application, we find that, for the given dataset, the semiparametric stochastic frontier model which uses a quantity of permanent grassland area as a proxy of environmental output, is the most suitable for application.
Keywords: C14; C23; D24; Q12; 330; environmental output; stochastic frontier analysis; stochastic ray function; Translog; Polish dairy farms